Implementation of the "Shabāḥ Al-Khair Yā Ikhwānī" Program in Improving Speaking Skills at The Aliyah Level at Muḥammadiyyah Mu‘Allimīn Islamic Boarding School Sāwah Dāngkā: تنفيذ برنامج "صباح الخير يا إخواني" في ترقيّة مهارة الكلام للمرحلة الثّا نويّة بمعهد محمّدية المعلّمين بساواه دانكا - Yulia Sari; Yelfi Dewi (Ukazh : Journal of Arabic Studies, 2026)
The “Ṣabāḥu al-Khair yā Ikhwānī” program is one of the Arabic language learning programs designed to improve students' speaking skills at Mu'allimin Muhammadiyah Islamic Boarding School, Sawah Dangka. However, some students still experience difficulties in speaking Arabic due to limited vocabulary and lack of language practice. This study aims to describe the implementation of the “Ṣabāḥu al-Khair yā Ikhwānī” Program, explain its role in improving speaking skills, and identify the supporting and inhibiting factors affecting its implementation. This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and then analyzed through data reduction, data display, and conclusion drawing. The results showed that the program was implemented systematically every morning through vocabulary enrichment, expressions, and short dialogues using the simā‘ī wa al-muḥāfaẓah method, as well as storytelling performances every Saturday. The program contributed to improving students’ speaking skills by enhancing self-confidence, speaking fluency, vocabulary mastery, and the use of Arabic in daily communication. Supporting factors included students’ enthusiasm, institutional support, teacher collaboration, and a conducive language environment. Inhibiting factors included limited time, lack of activity variation, and the limited number of teachers with expertise in teaching speaking skills. Therefore, the implementation of the “Ṣabāḥu al-Khair yā Ikhwānī” program contributed positively to improving the speaking skills of eleventh-grade students at Mu'allimin Muhammadiyah Islamic Boarding School, Sawah Dangka.